Shearing Stress-Induced Lipid Accumulation in Chlorella Cultivated in CO₂-Enriched Medium Modified with NaOH - Ragil Pandu Sadewo; Devi Bentia Effendi; Nur Faiizah Aqiilah Firman; Putu Yudha Ugrasena; I Gusti Ayu Nadia Prasta Unique; Gema Puspa Sari; Khairul Anam (Science and Technology Indonesia, 2026)
Chlorella can produce MUFA and PUFA, such as linolenic acid, with an ideal ω-3: ω-6 ratio content (1:1). This study investigates the effects of centrifugation-induced shear stress on lipid metabolism and fatty acid composition in Chlorella sorokiniana and Chlorella vulgaris cultivated in CO2-enriched TAP medium modified with NaOH as an inorganic carbon source. Shear stress was applied during the exponential growth phase to assess its influence on biomass productivity, biochemical composition, and lipid accumulation under nutrient-rich (P1) and nutrient-deficient (P2) conditions. Results revealed that C. sorokiniana showed superior adaptability to shear stress compared to C. vulgaris, showing a 64.7% increase in lipid content and maintaining higher unsaturated fatty acid (UFA) proportions, particularly polyunsaturated fatty acids (PUFAs). In contrast, nutrient deprivation in P2 promoted saturated fatty acid (SFA) accumulation as an energy storage adaptation. Biomass recovery in P1 indicated the need for nutrient availability in sustaining growth following mechanical treatments. The fatty acid profile of C. sorokiniana was dominated by UFA (67.2%), including ω-3 and ω-6 PUFAs, whereas C. vulgaris showed a higher SFA (42.2%). These findings suggest that moderate shear stress can stimulate lipid biosynthesis and improve the nutritional quality of microalgal lipids without compromising cell viability, provided sufficient nutrients are available. The combination of shear stress induction and optimized nutrient management offers a promising strategy to enhance microalgal lipid production for functional food and nutraceutical applications.